Analisis Efektifitas Program Penurunan Stunting Di Mlangsen Kecamatan Blora Kabupaten Blora - Tri Lestari Hadiati; Risma Yulianti (Universitas 17 Agustus 1945 Semarang, 2024)
Kelurahan Mlangsen, Kec. Blora, Kab. Blora is one of the locations with stunting cases. Mlangsen is one of the target areas for implementing the stunting reduction programme policy, because there are still many children suffering from stunting (short stature, stunted body). The role of the posyandu team is very important in reducing stunting in Mlangsen. The stunting reduction programme carried out by the Mlangsen posyandu team, is by providing counseling and counselling to prospective mothers and mothers of toddlers about nutritional health and child food management once a month by going from house to house, distributing PMT (Supplementary Feeding) for 3 months, giving Vitamin A and Zinc to toddlers. The purpose of this study was to analyse the stunting reduction program in Mlangsen, Blora sub-district, Blora district. The type of research used is descriptive research, with the population being identified and positive stunting families in Mlangsen as many as 22 informants, namely 12 identified stunting family informants and 10 stunting family informants. The sampling technique used a census technique, the data collection technique was carried out by observation, interview, questionnaire & documentation. The data analysis technique used uses complementary descriptive qualitative methods, in order to produce strong data analysis to respond to various kinds of questions and research objectives, besides that it is equipped with percentage data. The results of this study conclude that the level of efficiency in achieving the objectives and precisely the target group of the stunting reduction programme is good / high, namely 72.5% based on the cumulative score calculation. In addition, the use of posyandu team resources and the infrastructure used to generate awareness of families at risk of stunting. The Stunting Reduction Programme is doing the rights things (Druker). Meanwhile, Duncan's 3 important points of effectiveness in the Stunting Reduction Programme in Mlangsen, namely in achieving programme objectives, integrating the programme and the adaptability of families at risk of stunting, the level of effectiveness is also good/high.